Effects of Particulate and Fibrous Carbon Filler Combinations on the Tribological Behavior of a Polyacetal Composite under Water Lubrication - Hiroaki Yoshida (Japanese Society of Tribologists, 2019)
This study focused on the effects of combinations of fillers comprising particulate and fibrous carbon materials on the tribological behaviors of a polyacetal (POM) composite under water lubrication. The filler materials were rice bran ceramics (RBC) particles and carbon fibers (CFs). Friction tests were conducted using a ring-on-disk-type friction tester under water lubrication and the ring specimen was an austenitic-stainless-steel ring. The RBC/CF composite exhibited the lowest friction coefficients (0.10–0.14) compared with the other composites, including pure POM, irrespective of the number of friction cycles. The CF composite produced a low friction coefficient during the initial stage of friction but then increased to 0.25. The wear volume of the RBC/CF composite was the smallest, irrespective of the number of friction cycles. The specific wear rate of the RBC/CF composite decreased over the wear periods, indicating a low value of 10−6 mm3/N·m at the end of the long-term friction cycles. Scanning electron microscopy observations and measurements of the surface geometries indicated that the combination of RBC particles and CFs produced the low friction and low wear because the RBC particles complemented the poor wear resistance of the CFs.